"All the Other Devils this Side of Hades": Black Banks and the Mississippi Banking Law of 1914. Issue 4 (2021) - Garrett-Scott, Shennette
Abstract : The realms of banking and finance reveal a far more complex approach to early twentieth-century African American activism than the conventional protest vs. accommodation paradigm. Whites' anxieties about Black economic and political autonomy melded into a peculiar alchemy of progressive zeal and white supremacy that professed the idealistic goal of protecting citizens from exploitative business practices but had the practical effect of destroying symbols of Black economic progress. The context that drove the opening of Black banks in Mississippi as "monuments of protest" also made Mississippi's new banking law a powerful tool with which state actors and even regular citizens could strike blows against African Americans' growing economic, social, and political agency.